Transparency in ovarian cancer clinical trial results: ClinicalTrials.gov versus PubMed, Embase and Google scholar - Anna Roberto; Silvia Radrezza; Paola Mosconi (BMC, 2018)
Abstract Background In recent years the question of the lack of transparency in clinical research has been debated by clinicians, researchers, citizens and their representatives, authors and publishers. This is particularly important for infrequent cancers such as ovarian cancer, where treatment still gives disappointing results in the majority of cases. Our aim was to assess the availability to the public of results in ClinicalTrials.gov, and the frequency of non-publication of results in ClinicalTrials.gov and in PubMed, Embase and Google Scholar. We collected all trials on ovarian cancer identified as "completed status" in the ClinicalTrials.gov registry on 17 January 2017. We checked the availability of the results in ClinicalTrials.gov and systematically identified published manuscripts on results. Results Out of 2725 trials on ovarian cancer identified, 752 were classified as "completed status". In those closed between 2008 and 2015, excluding phase I, the frequency of results in ClinicalTrials.gov was 35%. Of the 752 completed studies the frequency of published results in PubMed, Embase or Google Scholar ranged from 57.9% to 69.7% in the last years. Conclusions These findings show a lack of transparency and credibility of research. Citizens or patients' representatives, with the medical community, should continuously support initiatives to improve the publication and dissemination of clinical study results.